MODEL STRATEGIC PLACES TRIANGLE UNTUK PENGEMBANGAN KAWASAN PARIWISATA - Muchammad Nurif (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
This research conducts on analysis of changes in the external environment of tourist destination especially for Kota Batu Malang District (East Java Province). The result of mapping analysis of the external environment shows factors that influence the condition, such as technological changes, the changes on regulation policy, socio-cultural changes, economical changes, and market changes. The analysis of internal environment of tourist destination in Kota Batu Malang results some influencing factors, namely a) nearness to Surabaya as the centre of government and economy, b) bureaucratic government system, c) the growth of industrial and tourism sector after agriculture. The use of Strategic Place Triangle approach and SWOT analysis results Positioning, Differentiation, and Brand of Kota Batu Malang tourism area. The Positioning of Kota Batu Malang tourism area is Bali of East Java that still holds religious values and local culture. The Differentiation is one-stop-shopping services, endless tourism enchantment, natural beauty, welcoming people, fame and enchant. The Brand of Kota Batu Malang tourism area is Enchantment of Kota Batu Malang Tourism.